2021
DOI: 10.3389/fphar.2021.605994
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Biological Activities and Biosynthetic Pathway of Dendrobium Alkaloids

Abstract: Dendrobium is a genus of flowering plants belonging to the Orchidaceae family with more than 1,400 species. Many Dendrobium species have been used as medicinal plants in several Asian countries for thousands of years. Alkaloids were reported as the major biological markers due to their complex chemical compositions and various types. In this review, we summarized the structural types of alkaloids, their pharmacological activities, as well as the mechanisms of biological activities. More than sixty alkaloids we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 70 publications
(65 reference statements)
1
41
0
Order By: Relevance
“…Previous studies have clearly shown that DSAs possess a variety of medicinal properties (Wang S. S. et al, 2020;Mou et al, 2021). The content of DSAs in Dendrobium is affected by several factors, such as Dendrobium type, stalk position, cultivation condition, and harvest period.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have clearly shown that DSAs possess a variety of medicinal properties (Wang S. S. et al, 2020;Mou et al, 2021). The content of DSAs in Dendrobium is affected by several factors, such as Dendrobium type, stalk position, cultivation condition, and harvest period.…”
Section: Discussionmentioning
confidence: 98%
“…Chemical modification catalyzed by enzymes is responsible for structural diversity in alkaloids, such as CYP450-mediated oxidation and hydroxylation reactions. Cytochrome P450 (CYP450) enzymes, belonging to a superfamily of monooxygenase, have been identified in Dendrobium genus ( Mou et al, 2021 ). Working on MeJA-induced alkaloids accumulation in D. officinale , Chen and associates ( Chen et al, 2019 ) identified 59 CYP450s involved in alkaloids biosynthesis through phylogenetic tree and gene expression pattern analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaloids with complex chemical structures consist of pyrrole, indolizidine, terpenoid alkaloids, amine alkaloids, indole, quinazoline, and others are the most common active compounds in D. nobile and are found in all parts of the plant [ 7 ]. Modern pharmacology studies have shown that alkaloids can relieve pain, have antipyretic effects, reduce heart rate and blood pressure, slow down respiration, and alleviate barbiturate poisoning [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%